Serological diagnosis of toxoplasmosis and determination of seroprevalence of anti-toxoplasma gondii antibodies in cattle in bursa province - Engin Kennerman; Güney Kaya; Serkal Gazyağcı; Cahit Babur; Selçuk Kılıç (Eurasian Journal of Veterinary Sciences)
Serological diagnosis of toxoplasmosis and determination of seroprevalence of anti-Toxoplasma gondii antibodies in cattle in Bursa province were aimed in this study. The material of the study was consisted of randomly selected twohundred healthy Holstein cattle aged 2 month - 5 year from six different districts in Bursa province. Clinical examinations were performed and blood samples were collected from all cattle. Anti-Toxoplasma gondii antibodies were analyzed with Sabin Feldman test. Anti - T. gondii antibodies were detected in 146 (73%) of 200 cattle and 54 (27%) cattle were found seronegative. Higher seropositivity was observed in Keles (86.2%) whereas lower se-ropositivity was found in Central district (63%). No difference was detected in hematological analysis of seropositive and seronegative cattle. As a result, it was determined that seroprevalance of toxoplasmosis was high in cattle in Bursa region and it was found that young cattle were more susceptible to infection in this study. It was concluded that prophylactic procedures must be performed in cattle against toxoplasmosis which is an important zoonotic infection for public health.